Genomewide analysis of the lateral organ boundaries domain gene family in Eucalyptus grandis reveals members that differentially impact secondary growth. Issue 1 (25th July 2017) - Lu, Qiang; Shao, Fenjuan; Macmillan, Colleen; Wilson, Iain W.; van der Merwe, Karen; Hussey, Steven G.; Myburg, Alexander A.; Dong, Xiaomei; Qiu, Deyou
Summary: Lateral Organ Boundaries Domain (LBD) proteins are plant‐specific transcription factors playing crucial roles in growth and development. However, the function of LBD proteins in Eucalyptus grandis remains largely unexplored. In this study, LBD genes in E. grandis were identified and characterized using bioinformatics approaches. Gene expression patterns in various tissues and the transcriptional responses of EgLBDs to exogenous hormones were determined by qRT‐PCR. Functions of the selected EgLBDs were studied by ectopically overexpressing in a hybrid poplar ( Populus alba  ×  Populus glandulosa ). Expression levels of genes in the transgenic plants were investigated by RNA‐seq. Our results showed that there were forty‐six EgLBD members in the E. grandis genome and three EgLBDs displayed xylem‐ ( EgLBD29 ) or phloem‐preferential expression ( EgLBD22 and EgLBD37 ). Confocal microscopy indicated that EgLBD22, EgLBD 2 9 and EgLBD37 were localized to the nucleus. Furthermore, we found that EgLBD22, EgLBD29 and EgLBD37 were responsive to the treatments of indol‐3‐acetic acid and gibberellic acid. More importantly, we demonstrated EgLBDs exerted different influences on secondary growth. Namely, 35S::EgLBD37 led to significantly increased secondary xylem, 35S::EgLBD29 led to greatly increased phloem fibre production, and 35S::EgLBD22 showed no obvious effects. We revealed that key genes related to gibberellin, ethylene and auxin signalling pathway as well as cell expansion were significantly up‐ or down‐regulated in transgenic plants. Our new findings suggest that LBD genes in E. grandis play important roles in secondary growth. This provides new mechanisms to increase wood or fibre production.